Unusual Presentation of Factor XII Deficiency with Bleeding: A Rare Case Report: LMRJ - Qadir, Fayal (LIAQUAT MEDICAL RESEARCH JOURNAL, 2020)
Factor XII (FXII) is a coagulation protein involved in the initiation of coagulation via contact activation system. Congenital FXII deficiency is a rare, asymptomatic disorder, associated with an isolated prolonged activated partial thromboplastin time (APTT). FXII deficiency is not commonly associated with any bleeding symptom except for a few cases presenting with occasional minor bleeds, which do not require treatment. Instead, a few literature reports suggest an increased incidence of various thromboembolic events in these patients. We report a rare occurrence of FXII deficiency presenting with severe bleeding symptoms.